Pemberdayaan Wanita Mendukung Strategi Gender Mainstreaming dalam Kebijakan Pembangunan Pertanian di Perdesaan - Roosganda Elizabeth (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2007)
EnglishModernization paradigm in the implementation of agricultural development has caused various changes in rural society, namely changes in social life, culture, politic, and especially economic structure in rural areas. This phenomenon also caused trend of disintegration and discrimination in “labor division” between male and female in various fields which could potentially set aside or even eliminate the important productive function of woman. This article is aimed at the description of many thoughts and ideas (by theory) about the role and the opportunity of woman who work in agriculture and repositioning the strategy of gender mainstream within the rural agricultural development policies. The double role of women is clearly indicating the importance of the double sources of income for a household. Women potentials, either as a housewife or as an individual of agricultural worker is the important factor to determine the success of gender mainstreaming strategy. The empowerment is suggested through applied and innovative technology, protection of working woman, improvement of training and extension activities, enhancement of regulations, facility support, increasing wage rate, and household industry skill development. Job opportunity is suggested to balance between male and female and encourage woman to participate in various development activities. With this, the gender mainstreaming strategy would improve household welfare in rural areas. IndonesianParadigma modernisasi dalam pelaksanaan pembangunan pertanian yang mengutamakan prinsip efisiensi, secara nyata telah mengakibatkan terjadinya berbagai perubahan pada masyarakat petani, baik struktur sosial, budaya dan politik terutama pada struktur ekonomi di perdesaan. Hal tersebut juga menimbulkan gejala desintegrasi dan diskriminasi dalam “pembagian kerja” antara pria dan wanita di berbagai bidang, yang dikhawatirkan dapat meminggirkan bahkan menghilangkan fungsi produksi kaum wanita. Makalah ini bertujuan mengemukakan berbagai pemikiran (teoritis) tentang peran dan peluang wanita tani, serta memposisikan kembali strategi pengarusutamaan gender (gender mainstreaming) dalam strategi kebijakan pembangunan pertanian di perdesaan. Peran ganda wanita tani membuktikan sangat penting dan strategisnya pola nafkah ganda, sebagai upaya meningkatkan pendapatan. Potensi wanita tani, sebagai isteri dan ibu rumah tangga, merupakan faktor penting penentu keberhasilan strategi pengarusutamaan gender tersebut. Pemberdayaan perlu dilakukan melalui teknologi tepat guna dan inovatif, perlindungan terhadap tenaga kerja wanita, meningkatkan efektifitas penyuluhan dan pelatihan, perbaikan regulasi, fasilitas, dan tingkat upah, pelatihan dan pembinaan ketrampilan industri rumahtangga. Kesempatan kerja agar berimbang antar gender dan mengikutsertakan mereka dalam segala kegiatan pembangunan. Pemberdayaan wanita melalui strategi pengarusutamaan jender (gender mainstreaming), untuk mewujudkan kesejahteraan rumah tangga petani di perdesaan.